A 24-Hour Extended Calibration Strategy for Quantitating Tacrolimus Concentrations by Liquid Chromatography–Tandem Mass Spectrometry. (17th June 2021) - Brister-Smith, Allister; Young, Jeffrey A; Saitman, Alec
Abstract: Background: Tacrolimus has a low therapeutic index requiring strict control of whole blood concentrations. Although random access immunoassay platforms exist that rapidly provide quantitative values for tacrolimus, LC–MS/MS may provide more accurate quantitation. However, batch testing in many LC–MS/MS assays is not efficient, particularly when testing patients suspected of having tacrolimus toxicity. Extending calibration curve stability beyond the traditionally accepted single batch may facilitate improved turnaround time and reduce testing costs. A 24-h extended calibration of LC–MS/MS tacrolimus was designed and validated to reduce calibrator usage, improve turnaround time, and provide a more efficient workflow for urgent requests. Methods: Patient samples included in the study were extracted and assayed with coextracted calibrators and quality control in real time. The same patient samples were extracted again 24 h later without coextracted calibrators. The data acquired from the second patient sample extraction was applied to the original calibration curve acquired 24 h prior and compared to the data for the same samples coextracted with calibrators, creating a value set utilizing extended curve stability. Results: A linear regression compared the results using the extended curve to the results of the coextracted acquisitions. This yielded a strong correlation between the 2 data populations, with a slope of 1.0061 and a correlation coefficient of >0.95. The average bias between original patient values and patient values 24 h later was 3.4% across all patient samples. Conclusions: Patient tacrolimus values were comparable when extracted within 24 h of calibration versus values coextracted with calibrators. Demonstrating comparability within 24 h of calibration allows the laboratory to provide rapid turnaround time for urgent samples without the need for an entirely new calibration curve.